Pengaruh Intervensi Aktivitas Fisik Berbasis Komunitas dalam Mengurangi Risiko Obesitas pada Remaja: Meta Analisis - Marjes N. Tumurang (Poltekkes Kemenkes Padang, 2024)
Based on predictions in 2030, 38% of the world's adult population will be overweight and another 20% will be obese. Research objectives for community-based physical activity in reducing the risk of obesity in adolescents. Research Design is a meta-analysis that focuses on a comprehensive review of studies assessing the effectiveness of physical activity interventions in reducing the risk of obesity in adolescents aged 10-19 years published up to May 2024. Important aspects looked at are the type of intervention, participants, outcomes, study design . For the literature search, electronic scientific databases such as PubMed, Scopus, Web of Science, and Google Scholar were systematically explored. The search used the keywords